Positive education in light of the manifestations of the beautiful names through (messages of light) - دلدار غفور حمدامين الكُ األستاذ الدكتور رد ّي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
(Al-NurLetters) is a sincere and faithful educational attempt to build a wide and strong base of positive education and faith knowledge, which gives its students and followers a stability and resistance to face the negativities of worldly life, which might be material or emotional. Then, they proceed to spread virtues, peace and goodness with sincerity in intention and good deed. Al-Nawurasy (may his soul rest in peace) has addressed in his thesesthe theoretical occurrence in Allah’s names in our behaviors with the surroundings that we live in. His theories are based on interactions, affectionsand many others. They make the humans and their educations as subjects for these occurrences. This is because humans are the highest creatures of Allah Almighty. Thus, here we have to stop on the obstacles that appear in these occurrences. This study takes some names of Allah Almighty as examples to illustrate the topic of the paper.